The Emperor's revenge [large type] / an Oregon Files adventure - Cussler, Clive; Morrison, Boyd, 1967- (Cussler, Clive. Oregon files adventures, 2016)
When a violent bank heist during the Monaco Grand Prix decimates the Corporation's accounts, Juan joins forces with an old friend from his days in the CIA so they can track down a rogue hacker and a ruthless former Ukrainian naval officer. It is only after the hunt begins that the enormity of the plan comes into focus: the bank theft is just the first step in a plot that will result in the deaths of millions and bring the world's economies to a standstill. The catalyst for the scheme? A document stolen during Napoleon's disastrous invasion of Russia ... and two hundred years later, it may be the thing that brings Europe to its knees.